Tradisi Salaman Masyarakat Pringgolayan Dalam Tinjauan Etika Nilai Max Scheler - Tamam, Badrud (Mozaic: Islamic Studies Journal, 2025)
One of the important things in the tradition of shaking hands is understanding its context. Some regions have specific meanings in carrying it out. The purpose of this study is to determine the value of the tradition of shaking hands using ethical philosophy research (Living Philosophy). In addition, this research is examined because some people view it from the perspective of religious doctrine. This study uses qualitative research with descriptive-analytical methods, utilizing observation, interview, and documentation approaches, targeting the community in Pringgolayan, Bantul, Yogyakarta. The research then found that the local community has very strong family and brotherhood values. Evidenced by the similarity of opinions and references from each informant. The Pringgolayan community realized that there was a change after seeing that the environmental conditions that were previously urban individualistic, then shifted to a society with socialism. The tradition of shaking hands then became a permanent culture with a high sense of harmony between individuals. This study confirms a harmony between individuals. And the new value that can be taken is a self-respect for fellow community members without regard to social status and background of each individual.